2018
DOI: 10.4103/ortho.ijortho_295_17
|View full text |Cite
|
Sign up to set email alerts
|

Exposed versus Buried Kirschner Wires Used in Displaced Pediatric Fractures of Lateral Condyle of Humerus

Abstract: Background:Comparision of results and complications of exposed versus buried Kirschner wires (K-wires) after open reduction of lateral condyle fractures is scarce and mainly from western population; hence, we envisaged to study the safety and efficacy of exposed and buried K-wires used for fixation of displaced pediatric fracture of the lateral condyle of humerus in Indian setup.Materials and Methods:A prospective, nonrandomized, comparative study was conducted in 50 patients with age <12 years, presenting wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 25 publications
1
12
1
Order By: Relevance
“…Mean extension lag of elbow was 7.7° in group 1 and 9.8° in group 2 (P = 0.026); however, it continued to improve in most of the children after 3 months. Thus we believe the outcomes, mostly achieving a stable fixation and long-term postoperative range of movements of both the surgical techniques were nearly the same, which is in accordance with most of the published studies [8][9][10][11][12][13][14].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Mean extension lag of elbow was 7.7° in group 1 and 9.8° in group 2 (P = 0.026); however, it continued to improve in most of the children after 3 months. Thus we believe the outcomes, mostly achieving a stable fixation and long-term postoperative range of movements of both the surgical techniques were nearly the same, which is in accordance with most of the published studies [8][9][10][11][12][13][14].…”
Section: Discussionsupporting
confidence: 89%
“…After preliminary reduction, K-wires were used for definitive fixation under fluoroscopic guidance. For exposed wires, we pierced the skin through a separate stab incision without drilling directly to avoid skin necrosis and subsequent risk of infection [13]. Wires were cut, bent and kept exposed with the ends outside the skin in group 1, and buried under subcutaneous tissue in group 2.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 13 studies met inclusion criteria with a combined total of 1299 patients 14,[17][18][19][20][21][22][23][24][25][26][27][28] (see Table 1). Table 2 shows how many patients and the number of studies were used for each measure.…”
Section: Resultsmentioning
confidence: 99%
“…Various studies also reported similar complication and were also managed accordingly. 8,12,19,21 One of theother notable complication of open reduction and internal fixation of lateral condyle fracture is the lateral prominence or the lateral spurring which is a distinct radiological finding and is rarely symptomatic. The development of the lateral spur depends upon the degree of initial fracture displacement, the amount of periosteal dissection done and the stability of fracture fixation.…”
Section: Discussionmentioning
confidence: 99%